The handbook for aspiring higher education leaders - Tomlin, Antione D. (Research, theory, and practice within academic affairs., 2024)
"The aim of this book is to allow past and present higher education leaders to offer wisdom and advice for new and potential leaders. Each chapter author shares experiences, strategies, and recommendations for both academic and student affairs leaders across divisions and departments to help new and aspiring leaders on their journey to success. While there is no one true definition of leadership, we hope this text will add to the conversation about impactful and effective leadership. Each chapter is rich in knowledge and perspective that support the current and next generation of leaders. We approach this book as a handbook, where chapter authors reflect upon their journeys to glean insight and wisdom. Each chapter is formatted in a similar way. Each author details their unique journeys into their respective fields, trajectory to leadership, and experiences that helped shape their leadership approaches. Then, the authors look back to discern advice they would share with themselves as new higher education leaders and what (if anything) they would do differently. Lastly, the authors share rich tips, strategies, and recommendations for new and potential higher education leaders on achieving success in the field. We are confident that there will be a notion or practice within these chapters to support all who read. Chapter authors are from a variety of disciplines. We see this book as a volume that can be used by practitioners and aspiring practitioners across the nation as inspiration to higher education leaders on navigating careers in higher education and how to be an effective leader. Throughout the book, we offer four themes that provide more insight into tips, strategies, and recommendations for new and potential higher education leaders on how to achieve success in the field. While each chapter in this book follows the structure mentioned above, the themes illuminate the experiences of higher education leaders and their individual and collective journeys"--